The Impact of Internet Addiction and Family Communication Patterns on Reproductive Health and the Risk of Sexual Violence Among High School Boys in Yogyakarta, Indonesia - Rahman, Abd; Urbayatun, Siti; Arifuddin, Adhar; Nur, A Fahira (YCAB Publisher, 2025)
The study aimed to examine the role of internet use addiction and family communication patterns on the tendency to experience sexual violence in Boys students in Yogyakarta. The design of this research is quantitative research. The sample size in this study was 380 students at high school/vocational studentsYogyakarta. The sampling technique is cluster random sampling. The measuring instruments used were the Child Sexual Abuse Questionnaire (CSAQ), the Internet Addiction Test (IAT), and the family communication patterns questionnaire, which the author had modified. The analysis used is linear regression analysis using R version and Python. The results of the study based on the simultaneous test obtained a value of F = 17.111 and p-value = 0.000 <0.05, the results indicate that addiction to internet use and family communication patterns simultaneously play a very significant role in the tendency to experience sexual violence against boys student high school/vocational in the Yogyakarta. Internet use addiction plays a significant role in the propensity to experience sexual violence. This means that the higher the habit of male students using the Internet, the more likely they are to experience sexual violence. Meanwhile, although it plays a role simultaneously, the family communication pattern does not affect the tendency to experience sexual violence in boys student high school/vocational in Yogyakarta.